Implementasi Komik Digital dalam Meningkatkan Kemampuan Siswa Membaca Descriptive Text di MI Oku Timur - Zulaikah Zulaikah; Ahmad Ulin Niam; Nindy Devita S.; Hastuti Retno K.; Widia Agustiani (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The learning process will be effective when supported by various planning, including the use and utilization of instructional media. The objective of this research is to determine the influence of using digital comic media on the intensification of reading abilities in descriptive English texts among students at MI Subulussalam in OKU Timur. The method used is an experimental approach, with data collection through oral tests based on topics within comic images. Based on the research results, it can be concluded that the implementation of Digital Comic instructional media has an impact on the ability to read descriptive texts compared to before the implementation of digital comic instructional media. This is evident from the difference between the pre-test and post-test results.